EXAMINATION OF THE IMMUNOGLOBULIN M ANTI SALMONELLA IN DIAGNOSIS OF THYPOID FEVER - Septiawan, I Kadek; Herawati, Sianny; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Typhoid fever is an acute systemic infectious disease caused by Salmonella typhi , that can be found all over the world. According to the world health organization ( WHO ) 2003, is predicted there are about 17 million cases of typhoid fever in the entire world with incidence 600,000 cases of deaths every year. The diagnosis of typhoid fever is done clinically and by laboratory examination. Laboratory examination can be an examination of the blood test, serological test, and culture. Examination of the IgM anti Salmonella (TUBEX ® test) is one of the new serological test which more quickly and accurately in diagnose typhoid fever. This examination is competitive agglutination test, semi quantitative, simple, quick and very accurate in the diagnosis acute infection of typhoid fever as it only detects the antibodies IgM Anti-Salmonella in a few minutes.
Keywords: typhoid fever, examination of the IgM anti Salmonella